THE ROLE OF GUIDANCE COUNSELING TEACHERS IN BUILDING STUDENTS' MORALS SUKAU MTs DARUSSOLIHIN INDRAPURA - Siti Maria Ulfa (UNISAN JURNAL, 2024)
This research aims to determine the role of the teacher in improving students at the school. This type of research is descriptive qualitative using the methods: 1. Observation, 2. Interview, 3. Documentation. The data obtained was reduced and then analyzed. The results of the analysis were obtained by the role of the teacher. The role of guidance and counseling teachers in developing students' morals is very vital in the educational context. Based on the discussion above, it can be concluded that: 1. Guidance and counseling teachers have the responsibility to accompany, guide and provide counseling to students in developing good morals. 2. They plan and implement moral development programs in schools, as well as provide solutions to problems or conflicts related to morals. 3. As role models and role models for students, guidance and counseling teachers must demonstrate good behavior and inspire students to follow in their footsteps. 4. In addition, they help students to develop an awareness of moral values ​​and independence in choosing actions that are in accordance with the desired morals. 5. Collaboration with parents and the community is also part of their role, in order to provide the support and information needed to develop student morals. By carrying out these roles effectively, guidance and counseling teachers contribute greatly to forming the character of students who have noble and responsible morals in everyday life.